PENGARUH MANAJEMEN WAKTU TERHADAP PRESTASI BELAJAR MAHASISWA PENDIDIKAN EKONOMI STAMBUK 2018 UNIMED (Manajemen & Bisnis Jurnal, 2022)
This studi aims to determine the effect of time management on student achievment in economics Education at the State University f Medan. The type of research is quantiative research using IBM SPSS version 22. Data collection techniques are through questionnaries, observation and documentation. The result of the study show that there is a positive and significant effect of time manjement on learning achievment with t acount of 5,264 which is greater than t table of 1,990.